Elemen Fasad Bangunan Pembentuk Karakter Koridor Jalan Ahmad Yani Garut Berdasar Preferensi Masyarakat - Anto Sudaryanto; Maria Immaculata Ririk Winandari (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2023)
The corridor of Jalan Ahmad Yani, as the main street of Garut Regency, is part of Garut Heritage sites. As a historical place, the area’s character becomes an important part. This study aims to find the building facade elements that formed the character of the Jalan Ahmad Yani corridor. Quantitative method with Conjoint is used to analyze and interpret data. Respondents consist of 20 architects that live in Garut. Massing shape, roof shape, walls, door and window openings, ornaments or billboards, texture, and color are the variables studied. The study found that the facade elements that are considered important in forming the character of the corridor, are geometric shapes, triangular roof shapes, mixed walls of solid and transparent, smooth textured, and calm colors, the shape of window openings pointing vertically and doors that balanced in the façade composition, and ornaments or billboards as part of the building façade composition.